2015
DOI: 10.3109/13880209.2015.1055634
|View full text |Cite
|
Sign up to set email alerts
|

A flavonoid compound fromChrysosplenium nudicauleinhibits growth and induces apoptosis of the human stomach cancer cell line SGC-7901

Abstract: Context: Gastric cancer remains highly prevalent, but treatment options are limited. Natural products have proved to be a rich source of anticancer drugs. Chrysosplenium nudicaule Ledeb. (Saxifragaceae) is a perennial herb that grows in the highlands of China. It has been used as a traditional Chinese medicine to treat digestive diseases for hundreds of years. Recent studies revealed that this herb had anticancer activity, and the flavonoids were speculated to be the effective components. 6,7,3 0 -Trimethoxy-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The most distinctive marker of MMP is the dissipation of the mitochondrial transmembrane potential (Δψ). Δψ results from the asymmetric distribution of protons and other ions on both sides of the inner mitochondrial membrane, thus creating a chemical (pH) and electric gradient that is essential for mitochondrial function (13). Cells undergoing apoptosis exhibit a decreased Δψ (14).…”
Section: Discussionmentioning
confidence: 99%
“…The most distinctive marker of MMP is the dissipation of the mitochondrial transmembrane potential (Δψ). Δψ results from the asymmetric distribution of protons and other ions on both sides of the inner mitochondrial membrane, thus creating a chemical (pH) and electric gradient that is essential for mitochondrial function (13). Cells undergoing apoptosis exhibit a decreased Δψ (14).…”
Section: Discussionmentioning
confidence: 99%
“…6, 7, 30-trimethoxy-3, 5, 40-trihydroxy flavone (TTF), extracted from Chrysosplenium nudicaule Ledeb. Herba, is a well known traditional Chinese medicine for digestive diseases [49]. TTF induced apoptosis on SGC-7901 cells treated at the dose of 2, 4, 8, 16, 32 μg/mL for 24, 48 and 72 h. Sun et al observed that curcumin, isolated from Curcuma longa L. Rhizoma (Zingiberaceae), induced apoptosis of SGC-7901 and BGC-823 (5, 10, 15, 20, 40 μM for 24 h) cells by up-regulating microRNA-33b (miR-33b) expression [50].…”
Section: Apoptosis-inducing Natural Molecules In Gastric Cancermentioning
confidence: 99%
“…Chrysosplenium is divided into two subgenera according to the leaf arrangement: Alternifolia Franchet with alternate leaves and Oppositifolia Franchet with opposite leaves [4,8,10]. Some species within the genus have been used in traditional Tibetan medicine to treat digestive system diseases [11].…”
Section: Introductionmentioning
confidence: 99%